Big Data Analytics in Healthcare: Transforming Diagnosis and Treatment - Mohammed Abdul Khaled (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Big Data analytics is revolutionizing healthcare by enhancing diagnosis, treatment, and patient outcomes through predictive analytics, machine learning, and artificial intelligence (AI). This paper explores the transformative role of Big Data in healthcare, focusing on its applications in clinical decision support systems, personalized medicine, and population health management. Challenges such as data integration, privacy concerns, and AI biases are discussed, along with emerging solutions and future trends in healthcare technology. The paper provides a roadmap for overcoming these challenges, highlighting the potential of Big Data to drive improvements in healthcare delivery, operational efficiency, and patient care. DOI: https://doi.org/10.17762/ijisae.v10i3s.8350